Parish Civil Society (An Analysis of Swedish Case) - Pivoras, Saulius (Sociologija. Mintis ir veiksmas, 2001)
This article deals with the paradoxical from the theoretical point of view phenomena – civic political culture in the Swedish parishes. It is assumed that civic political culture is not only and mostly connected with the participation in national political struggles, but active involvement, cooperating with neighbours, into the local public affairs. Swedish political culture is now labeled as consensual, but as such it rests upon the foundations, which were laid down by the collective communal order or so called “communalism” of the 19 th century. Article is mainly based on the analysis of protocolles from the parish or village community meetings (sockenstämmor and bystämmor). These protocolles one can find in the Umeå, Skellefteå and Härnösand archives. It is attempted to throw light on the specificity of village vommunity in Northern Sweden, to disclose features of of its organizational flexibility and to trace impact of lutheran church on the emergence of civic communality. Article shows as well main Lithuanian differences from Sweden in the sphere of communalism.